OSWALD SPENGLER AND PRUSSIAN SOCIALISM - Dostanić, Dušan (Serbian political thought, 2024)
In this the article, author examines Oswald Spengler’s concept of Prussian socialism. In the first part of the work, Spengler is presented as a political writer, and his political thought is connected with his philosophical ideas. As a political writer, Spengler belonged to the stream of conservative revolution. In the second part, the author tries to emphasize the difference between this current of conservative thought and liberal conservatism, pointing out that the roots of Spengler’s understanding of socialism lie in the older conservative criticism of the market. In the last part, the author considers Spengler’s conservative understanding of socialism, its influence on the German conservative revolution, and its importance in today’s times.